Endogenous fluctuations of OCT4 and SOX2 bias pluripotent cell fate decisions - Daniel Strebinger; Cédric Deluz; Elias T Friman; Subashika Govindan; Andrea B Alber; David M Suter (Molecular Systems Biology, 2019)
Abstract SOX2 and OCT4 are pioneer transcription factors playing a key role in embryonic stem (ES) cell self‐renewal and differentiation. How temporal fluctuations in their expression levels bias lineage commitment is unknown. Here, we generated knock‐in reporter fusion ES cell lines allowing to monitor endogenous SOX2 and OCT4 protein fluctuations in living cells and to determine their impact on mesendodermal and neuroectodermal commitment. We found that small differences in SOX2 and OCT4 levels impact cell fate commitment in G1 but not in S phase. Elevated SOX2 levels modestly increased neuroectodermal commitment and decreased mesendodermal commitment upon directed differentiation. In contrast, elevated OCT4 levels strongly biased ES cells towards both neuroectodermal and mesendodermal fates in undirected differentiation. Using ATAC‐seq on ES cells gated for different endogenous SOX2 and OCT4 levels, we found that high OCT4 levels increased chromatin accessibility at differentiation‐associated enhancers. This suggests that small endogenous fluctuations of pioneer transcription factors can bias cell fate decisions by concentration‐dependent priming of differentiation‐associated enhancers.